Corruption in the health sector: characteristics, some of its typologies and effects - Ramírez Cosme, Alexis Gustavo (2024)
In this research, the author approaches corruption linked to the health sector, treating the characteristics that make up its occurrence in the health system, thereby answering the question of why the health system is so attractive for acts of corruption. Then, some of the most important criminal typologies that national and international experience have brought to light are presented, analyzing their details and their relationship with the agents of the health system. Finally, scope is provided on the effects that this scourge has on society, providing notes in order to anticipate the problem.